Analisis Prospektif Strategi Pengembangan Sumber Daya Manusia Di Era Revolusi Industri 4.0 Pada BAPPEDALITBANG - Zakiyah Ulfa Aryani; Harapan Tua Ricky Fredy Simanjuntak; Dadang Mashur (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
The 4.0 industrial revolution is changing global work patterns, resulting in industrial displacement, and encouraging the development of digital literacy and HR competencies. Bappedalitbang has a critical role in regional development planning, and is closely aligned in addressing the digital skills gap. This research aims to analyze prospective HR development strategies in the era of the industrial revolution 4.0 at Bappedalitbang Riau Province. Respondents in this study amounted to 12 people who were used as key informants with purposive sampling method. This research analysis uses the prospective analysis method. The software used is Microsoft Excel which is modified with a prospective analysis calculation. After conducting a combined perspective analysis of theory and stakeholders, the results obtained 3 determining factors among 2 of the theoretical dimensions, namely managing technology integration in the workplace and building an agile and personalized learning culture and 1 stakeholder dimension, which is modern e-learning. These three factors must be applied so that human resource development in the era of the industrial revolution 4.0 at Bappedalitbang Riau Province can be sustainable.